2019
DOI: 10.3390/w11122626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Depth and Phosphorus Availability on Nitrogen Removal in Agricultural Wetlands

Abstract: Excess nitrogen (N) from agricultural runoff is a cause of pollution in aquatic ecosystems. Created free water surface (FWS) wetlands can be used as buffering systems to lower the impacts of nutrients from agricultural runoff. The purpose of this paper was to evaluate critical factors for N removal in FWS wetlands receiving high nitrate (NO 3 − ) loads from agriculture. The study was performed in 12 experimental FWS wetlands in southern Sweden, receiving drainage water from an agricultural field area. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Nevertheless, the agricultural drainage water can be a source of diffuse pollution in aquatic ecosystems due to high concentrations of nitrate, certain salts, phosphorus, organic nitrogen, pesticides and sediments (Woltemade, 2000;Haverstock et al 2017), as confirmed by the authors from different parts of the world (Tanner and Kadlec, 2013;Darwiche-Criado et al 2017;Mendes et al 2018a;Song et al 2019). Particularly, P enrichment in runoff leads to eutrophication harmful to plants growth (Johannesson et al 2017;Lavrnić et al 2018), and it can even result in toxic algae blooms and loss of biodiversity (Reinhardt et al 2005).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Nevertheless, the agricultural drainage water can be a source of diffuse pollution in aquatic ecosystems due to high concentrations of nitrate, certain salts, phosphorus, organic nitrogen, pesticides and sediments (Woltemade, 2000;Haverstock et al 2017), as confirmed by the authors from different parts of the world (Tanner and Kadlec, 2013;Darwiche-Criado et al 2017;Mendes et al 2018a;Song et al 2019). Particularly, P enrichment in runoff leads to eutrophication harmful to plants growth (Johannesson et al 2017;Lavrnić et al 2018), and it can even result in toxic algae blooms and loss of biodiversity (Reinhardt et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…SFCW systems are designed using parameters like water depth, size, substrate, plant, etc., and implemented under various requirements (e.g. flow rate, feeding mode) (Headley et al 2013;Morató et al 2014;Herrera-Melián et al 2018;Song et al 2019). However, factors like seasonal and annual variation, the aging of CW systems or other internal/external conditions have a possibility to negatively affect the treatment performance of CWs, particularly over the longer time periods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations